2020
DOI: 10.37706/ijaz.v5i1.205
|View full text |Cite
|
Sign up to set email alerts
|

Does Zakat Signal the Firm Value?

Abstract: Mining and manufacturing industries are two contributive sectors having high economic value. Optimalization of their zakat potential should be estimated not only addressed to provide the gain for public welfare, but firms should also obtain the economic value on their performance. This research aims to provide an empirical inference on mining and manufacturing zakatnomics. The effect of corporate zakat potential on the firms value is tested in this research. The sample comprises 47 mining companies and 180 man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 10 publications
1
7
0
1
Order By: Relevance
“…These findings encourage Islamic banks to focus on CSR, especially on zakat contributions to ameliorate the Islamic bank's financial performance. This idea has been underlined by Abbas (2020) who highlighted the relationship between zakat and firm value and profitability. In addition, the author indicates that zakat contributions can be considered as a "reputation strategy" since it plays an important role in building a good business image with stakeholders that can help a firm to possess a highly positive trust in the market.…”
Section: Zakatmentioning
confidence: 98%
See 1 more Smart Citation
“…These findings encourage Islamic banks to focus on CSR, especially on zakat contributions to ameliorate the Islamic bank's financial performance. This idea has been underlined by Abbas (2020) who highlighted the relationship between zakat and firm value and profitability. In addition, the author indicates that zakat contributions can be considered as a "reputation strategy" since it plays an important role in building a good business image with stakeholders that can help a firm to possess a highly positive trust in the market.…”
Section: Zakatmentioning
confidence: 98%
“…In addition, the author indicates that zakat contributions can be considered as a "reputation strategy" since it plays an important role in building a good business image with stakeholders that can help a firm to possess a highly positive trust in the market. So, according to Abbas (2020), the sign of a firm's value or profitability or marketability is earned by zakat payment.…”
Section: Zakatmentioning
confidence: 99%
“…The signal given by the company can be a disclosure of financial statements or Good News if there is an increase in income/profitability that exceeds investor expectations (Kasznik & McNichols, 2002). A company sends a signal to investors with the purpose of showing that it is better than another company (Abbas, 2020;Abbas et al, 2015). In the case of this research, it can be concluded that signal theory is able to inform stakeholders regarding the value of firms.…”
Section: Signaling Theorymentioning
confidence: 99%
“…Zakat is a method of distributing public income in an equitable manner in order to reduce social inequality. Zakat, terminologically, means holy, growing, and maslahah (Abbas, 2012). Zakat is one of the pillars of Islam and is applied to people who have fulfilled the criteria for zakat (Yayuli et al, 2022).…”
Section: Introductionmentioning
confidence: 99%